Indirect determination of the 5'→3' and 3'→5' of the DNA-dependent DNA-polymerase function - Skripal', I.G.; Bezugly, S.V.; Babitschev, V.V. (Биополимеры и клетка, 1994)
Doxorubicin in the concentration of 1 mg/ml and streptonigrin in the concentration 1000 mg/ml each agent separately should by useful to determination of replicative (5'→3') or reparatlve (3'→5') function DNA-polymerase. This enzymes with 5'→3' fully inhibited by doxorubicine but net sensitive to action of streptonigrin in concentration substances mentioned above. And contraverse, DNA-polymerase with 3'→5' function don't sensitive to doxorubicin and it's activity depressed by streptonigrin.